Additive manufacturing aimed to soft robots fabrication: A review. (January 2021) - Stano, Gianni; Percoco, Gianluca
Abstract: In the 21st century, robotics has been revolutionized by a new perspective: robots made of soft materials mimicking nature show several advantages compared to hard robot counterparts, leading to the birth and quick spread of a new scientific field named soft robotics. Due to the unconventional materials used in soft robotics (not only soft materials but also conductive, magnetic, and other materials employed for soft robot actuation), the manufacturing process is the basis by which to obtain soft structures able to meet specific requirements and save time and cost. The present paper aims to give a review of the current use of additive manufacturing (AM) methods for the manufacturing of soft robots. AM, also known as 3D printing, is characterized by several features, such as the possibility to easily produce very complex geometries, which are well suited for soft robot fabrication. The authors, after providing a summary of the most used actuation systems in soft robots, classify the use of AM technologies in soft robotics, investigating the most important and recent works in this field, as a function of how these technologies are employed in the whole soft robot manufacturing cycle. With this in mind, the authors found three approaches to exploit AM in soft robotics: rapid mold fabrication (AM plays a passive role), hybrid (AM plays an active role but manufacturing technologies other than AM are still used), and total additive manufacturing (only AM technologies are used). Only the latter approach takes full advantage of AM, although the other two still provide benefits. With new developments in commercial 3D printing systems (machines and materials) aimed at the fabrication of soft and unconventional parts, AM is set to become the manufacturing technology of the future in the soft robotics field, overcoming traditional manufacturing methods such as molding and soft lithography.